The effect of severe malnutrition, and subsequent re-feeding on digestive function in human subjects, with special reference to gastric acid and pancreatic enzyme secretion, and protein synthesis - Winter, Trevor Anthony (Department of Medicine, 2014)
Severe malnutrition may adversely affect digestive function, and result in the difficulties frequently encountered when attempting to re-feef such patients. To investigate the effects of undernutrition, and subsequent re-feeding, on digestive function in human patients, severely malnourished patients were studies before, and after a period of intensive nutritional support.